The Relationship between Internet Addiction, Mental Health and Suicidal Behavior among Undergraduate Students in Malaysia - Nur Sabrina Zulkifli; Nor Firdous Mohamed (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The aim of this study is to determine the relationship between internet addiction, mental health and suicidal behavior among undergraduate students in Malaysia. Online survey method is used in this study. 150 undergraduate students were recruited through convenience sampling. There were three instruments used in this study which were The Internet Addiction Test (IAT), Mental Health Inventory-18 (MHI-18) and The Suicide Behavior Questionnaire Revised (SBQ-R). Descriptive analysis is conducted to determine the prevalence of university students with internet addiction. The results showed that undergraduate students with severe internet addiction was 5.3 %, while 51.3 % of the undergraduate student had moderate level of internet addiction, 28.7% of them had mild level of internet addiction and the rest were normal users of internet. Next, Pearson’s Correlation analysis showed that there is a low negative correlation between internet addiction and mental health (r_150 = -.27, p < 0.01). Furthermore, the Pearson’s Correlation analysis also showed that there is a weak positive correlation between internet addiction and suicidal behavior (r_150 = .23, p < 0.01). In conclusion, we can observe that internet addiction is significantly related to mental health and suicidal behavior. We need to take this issue more seriously as mental health is an important aspect in our life. Keywords: Internet addiction, Mental health, Suicidal behavior, Undergraduate students